The environmental rule of law in India - Mehta, D (2017)
This thesis offers a new conceptual framework—the environmental rule of law—to describe weaknesses in the development of Indian environmental law, and uses this description to critique the dominant discourse on environmental institutional reform. A secondary framework—fragmentation is also used to supplement the analysis of Indian environmental law. Part I develops the conceptual framework of the environmental rule of law by considering the special challenges that the inherent polycentric and interdisciplinary nature of environmental law present for commonly understood rule of law values such as clarity, certainty and consistency. It also relies on Jeremy Waldron’s conception of articulated governance to demonstrate that the rule of law is linked to the principle of separation of powers. This conception lays emphasis on the role of the three institutions of government—the legislature, the executive and the judiciary—in strengthening or weakening the rule of law. To determine institutional contribution to the rule of law, I develop three broad indicators to assess the legal quality of the instruments of each of these institutions of government. These indicators are: a) capacity of statutes to guide executive and judicial behaviour by goal-setting and balancing competing interests; b) the ability of the executive to make flexible yet reasoned decisions grounded in primary legislation; and c) the use of statutory interpretation and consistent standards of judicial review by the courts as they give effect to environmental rights and principles. Through the use of case studies in Part II that span environmental impact assessment, forest conservation, and indigenous rights, I demonstrate that the lack of adherence to these indicators produces a body of environmental law that is fragmented i.e. one characterised by multiple overlapping yet self-contained legal regimes with conflicting provisions and the absence of unifying norms. In Part III, I use this understanding of fragmentation to critically analyse environmental legal and institutional reform proposals. I show that existing proposals address only the structure, rather than the process of functioning of the institutions of government. The rule of law framework that I develop also has potential for application to other areas of the law.